1979
DOI: 10.1111/j.1365-2621.1979.tb09120.x
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF TIME AND CONDITIONS OF STORAGE ON TECHNOLOGICAL AND NUTRITIONAL PROPERTIES OF A DRY BEAN (Phaseolus vulgaris, L.) VARIETY ROSINHA G2

Abstract: The influence of storage on dry bean was studied for 6 months under three different conditions of temperature and relative humiditv (RH): A. 12°C. 52% RH: B. 25°C. 65-10% RH: and C. 37°C. 76% RH. Then hydration capacity of rhe seeds remained constant under condition A, increased slightly under condition C and decreased to less than 50% of the original under condition B. Changes in the percentages of hardshell beans were inversely proportional to the hydration capacity. The texture (hardness) of the cooked bean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 3 publications
1
22
0
2
Order By: Relevance
“…Methods used to measure water absorption, however, have not been standardized sufficiently to compare results of many published reports, and, therefore, the conditions promoting either HS or HTC defects are not always clear. Antunes and Sgarbieri (1979) found HS to be promoted by storage of beans at 2X/65-70% RH, however, this was not found to be reproducible by Hohlberg and Stanley (1987). In a botanical review by Rolston (1978), water impermeable seeds are considered seedcoat related, promoted by sudden drying and reversible by storage in higher humidity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Methods used to measure water absorption, however, have not been standardized sufficiently to compare results of many published reports, and, therefore, the conditions promoting either HS or HTC defects are not always clear. Antunes and Sgarbieri (1979) found HS to be promoted by storage of beans at 2X/65-70% RH, however, this was not found to be reproducible by Hohlberg and Stanley (1987). In a botanical review by Rolston (1978), water impermeable seeds are considered seedcoat related, promoted by sudden drying and reversible by storage in higher humidity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Liu et al (1992) found an increase in hardness of cowpea during 18 months at 30 °C/64% RH. Research studies show that long duration storage of pulses at elevated temperature and humidity results in a reduction of the hydration capacity, reduction of cooking quality (increase in cooking time), darkening, development of off-flavor and increased lipid acidity (Burr et al, 1968;Antunes and Sgarbrieri, 1979;Kon and Sanshuck, 1981) in common beans. However, bean quality can be maintained at low storage temperature (10-20 °C), moderate relative humidity (50% RH) and safe moisture content (10-14%) (Yousif et al, 2007).…”
Section: Effect Of Post-harvest Technology On Qualitymentioning
confidence: 98%
“…The limited availability of sulfur amino acids in legumes has been reported for several authors (Sarwar et al, 1977;Antunes and Sgarbieri, 1979). Evans et al, 1974 reported from rat studies that 49% of the methionine and 25% of the cystin?…”
Section: Introductionmentioning
confidence: 92%
“…These authors suggested the limited availability was due to a failure of the rat to digest and absorb some proteins or peptides which contain considerable amounts of the bean's sulfur amino acids. Antunes and Sgarbieri (1979) reported a decrease in methionine and cystine availability during storage of dry beans. Sgarbieri et al, (1979) reported only 2941% of the methionine to be bioavailable in four Brazilian varieties of dry beans.…”
Section: Introductionmentioning
confidence: 96%